Penerapan Catur Pramana Sebagai Metode Ilmiah Dalam Peningkatan Mutu Pembelajaran Agama Hindu - Ni Nengah Kerti (Jurnal Penjaminan Mutu, 2018)
In line with the implementation of the 2013 curriculum, the term scientific approach becomes the subject of discussion that attracts the attention of educators. Applying this approach becomes a teacher challenge through the development of student activities in learning, which in Hinduism is called catur pramana. This epistemology describes four ways to acquire and develop science, which can be called the Hindu scientific method. These ways are called prataykasa pramana. anumana pramana, upamana pramana and sabda pramana. Catur pramana can be applied in the learning of Hinduism and encourage the realization of student-centered learning. The application of scientific method of catur pramana in Hindu teaching aims to improve the quality of effective and enjoyable learning.